PENGARUH PENAMBAHAN SERBUK Al2O3 DAN Na2CO3 PADA KARAKTER TERMAL PREKUSOR Li4Ti5O12 - Slamet Priyono; Bambang Prihandoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Study on the effect of adding Al2O3 and Na2CO3 powder on thermal characteristic of Li4Ti5O12 precusor have been done. Li4Ti5O12 synthesized by using a mixture of Li2CO3 and TiO2 as raw materials through solid state method with calcination at 700 °C. The addition of a bit of the other material will affect the characteristics of the material, especially on the thermal properties. The study consisted of two variations, namely, Al2O3 powder was added to the mixture of Li2CO3/TiO2 and the second variation is Al2O3 powder and Na2CO3 was added to the mixture of Li2CO3/TiO2 and then analyzed by Simulthaneous Thermal Analysis (STA). Measurement of thermal properties include the decomposition temperature, enthalpy, and the determination of the calcination temperature. The measurement results showed that the addition of Al2O3 in the precursor decomposition temperature of Li4Ti5O12 provide 659 ° C, the enthalpy of 5.675 kJ / g and a calcination temperature of about 750 ° C. While the addition of Al2O3 and Na2CO3 on Li4Ti5O12 precursor gave decomposition temperature of 560 ° C, the enthalpy of 5.672 kJ / g and a calcination temperature of about 680 ° C. The addition of Al2O3 powder showed an increase of energy required for the synthesis while the addition of Na2CO3 powder showed a decrease in the energy required for the synthesis process. Keywords: thermal properties of Al2O3, STA, Na2CO3, Li4Ti5O12.